Budget of the EU and Common Agricultural Policy for 2014-2020 in the light of the polish interests = Budżet UE i wspólnej polityki rolnej na lata 2014-2020 w świetle interesów Polski - Czyżewski, Andrzej; Stępień, Sebastian (Zielona Góra: Faculty of Economics and Management Press)
The objective of the paper is to present the results of negotiations on the EU budget for 2014-2020, with particular emphasis on the Common Agricultural Policy. Authors indicate the steps for establishing the budget, from the proposal of the European Commission presented in 2011, ending with the draft of UE budget agreed at the meeting of the European Council on February 2013 and the meeting of the AGRIFISH on March 2013 and then approved by the political agreement of the European Commission, European Parliament and European Council on June 2013. In this context, there will be an assessment of the new budget from the point of view of Polish economy and agriculture.
Keywords: budżet UE; Wspólna Polityka Rolna; nowa perspektywa finansowa; rolnictwo polskie; EU budget; common agricultural policy; new financial perspective; Polish agriculture